Contracting under uncertainty: Groundwater in South India - Xavier Giné; Hanan Jacoby (Quantitative Economics, 2020)
To quantify contracting distortions in a real-world market, we develop and structurally estimate a model of contracting under payoff uncertainty in the south Indian groundwater economy. Uncertainty arises from unpredictable fluctuations in groundwater supply during the agricultural dry season. Our model highlights the tradeoff between the ex post inefficiency of long-term contracts and the ex ante inefficiency of spot contracts. We use unique data on both payoff uncertainty and relationship-specific investment collected from a large sample of well-owners in Andhra Pradesh to estimate the model's parameters. Our estimates imply that spot contracts entail a 3% efficiency loss due to hold-up. Counterfactual simulations also reveal that the equilibrium contracting distortion reduces the overall gains from trade by about 4% and the seasonal income of the median borewell owner by 2%, with proportionally greater costs borne by smaller landowners.
Keywords: L14; Q15; 330; Hold-up; relationship-specific investment; subjective probabilities; structural estimation